Inception: the creation of an international water management institute, 1969-1984 - Lenton, Roberto (International Water Management Institute, 2024)
This report describes the creation of the International Water Management Institute (IWMI) from early 1969 to late 1984. The report tells the story of how an ever-expanding circle of scientists, practitioners and funders joined forces over a 15-year period to co-create the institute that over time became the IWMI of today. It has been prepared as a supplement to the 40th anniversary publication titled Celebrating IWMI at 40: Learning from our History, Turning to the Future.